2020
DOI: 10.1111/imm.13171
|View full text |Cite
|
Sign up to set email alerts
|

CD8α conventional dendritic cells control Vβ T‐cell immunity in response to Staphylococcus aureus infection in mice

Abstract: Dendritic cells (DCs) are potent immune cells that control innate and adaptive immune responses. Previous studies have shown that the DCs are required for protection against Staphylococcus aureus infection. However, the role of conventional DC (cDC) subsets during S. aureus infection in vivo has not been well investigated. In this study, we examined the function of spleen DC subsets in the activation of immunity against S. aureus infection. C57BL/6 mice were infected intravenously with S. aureus and DC and T‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(89 reference statements)
2
1
0
Order By: Relevance
“…We observed that CD8 + T cells were not only activated through the recognition of their specific peptide at the surface of infected DCs but also in the absence of this peptide, albeit at lower levels. This is consistent with studies highlighting the role of superantigens, such as TSST-1, in the activation of T cells (Darisipudi et al, 2018;Balraadjsing et al, 2019;Zhang et al, 2020). Such an activation can also induce the anergy of T cells (O'Hehir and Lamb, 1990;Cornwell and Rogers, 2010), and therefore a failure of T cell response.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed that CD8 + T cells were not only activated through the recognition of their specific peptide at the surface of infected DCs but also in the absence of this peptide, albeit at lower levels. This is consistent with studies highlighting the role of superantigens, such as TSST-1, in the activation of T cells (Darisipudi et al, 2018;Balraadjsing et al, 2019;Zhang et al, 2020). Such an activation can also induce the anergy of T cells (O'Hehir and Lamb, 1990;Cornwell and Rogers, 2010), and therefore a failure of T cell response.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro, only BDCA1 + myeloid DCs are able to engulf S. aureus and strongly upregulate the expression of costimulatory molecules and production of proinflammatory cytokines, inducing T cell differentiation into IFN-g-producing CD4 + and CD8 + T cells (Jin et al, 2014). The capacity of DCs to internalize S. aureus and their ensuing maturation is consistent with previous results obtained in vitro (Balraadjsing et al, 2019) or in vivo (Zhang et al, 2020). This maturation could partly be due to the activation of the TLR2-MyD88 pathway after the recognition of S. aureus lipoproteins as shown in vivo (Schmaler et al, 2011;Darisipudi et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation